Self-Control, Parental Monitoring, and Adolescent Problematic Mobile Phone Use: Testing the Interactive Effect and Its Gender Differences - Hu, Yu-ting; Wang, Qing (Frontiers in Psychology, 2022)
Previous studies have revealed that self-control was one of the critical factors of adolescent problematic mobile phone use. Few studies, however, have explored the interaction of internal control force (i.e., self-control) and external control force such as parental monitoring. The present study tested the interactive effect of self-control and parental monitoring on adolescent problematic mobile phone use and its gender differences. A sample of 926 adolescents completed our anonymous self-report survey. Results showed that self-control and parental monitoring negatively predicted problematic mobile phone use, while gender positively predicted problematic mobile phone use. Self-control and parental monitoring had an interactive effect on problematic mobile phone use, with the effect of self-control on problematic mobile phone use being stronger for adolescents with low levels of parental monitoring than for those with high levels of parental monitoring. Self-control and gender had an interactive effect on problematic mobile phone use, with the effect of self-control on adolescent problematic mobile phone use being stronger in girls than in boys. Moreover, there were significant gender differences in the interaction of self-control and parental monitoring, in that the interactive effect of self-control and parental monitoring on problematic mobile phone use was more potent in girls than in boys. The findings reveal how the internal control force (i.e., self-control) and external control force (i.e., parental monitoring) work together in explaining adolescent problematic mobile phone use and uncover the potential gender differences in exploring adolescent problematic mobile phone use from the individual-environment perspective. Limitations and implications are discussed.